Molecules of an author in search of memory A civil-scientific play of two acts - Dei, Luigi (Firenze University Press, 2014)
Loosely based on Primo Levi's The Periodic Table, the play has a Fahrenheit 451 setting. In a world without books or memory appears a common man, the Man in the street, with some heets of writing that he cannot make out. With the help of the narrator, Science, Technology and Nature, and of two actors who remain offstage for a long while - Primo and his friend Alberto - this man is able to reconstruct the events of the chapter entitled Cerium. In this way, and thanks to this act of remembrance, lost identity - our history - is recreated. Science, Technology and Nature free this man without memory from his state of not-knowing, by giving him scientific knowledge and understanding. The play finds its catharsis in a deeply moving passage, inspired by the chapter Carbon, which creates an atemporal connection between a carbon atom from the smoke of a crematorium chimney and one residing in the body of any one of us: a poetic parable of a science firmly anchored in the life and history of man.